Environmental Awareness and Practices in YES-O Programs, Projects and Activities of Grade 10 Students - Eugenio, Windsor (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the environmental awareness and environmental practices of Grade 10 students in relation to the programs, projects, and activities of the Youth for Environment in Schools Organization (YES-O). Specifically, it described the profile of the respondents in terms of sex, school size, and school location, and determined their level of environmental awareness and environmental practices in the areas of School Inside a Garden, Awareness and Outreach Programs, Solid Waste Management, Entrepreneurship and Energy Conservation, Gulayan sa Paaralan, and Partnerships and Linkages. The study employed a quantitative descriptive design and involved 200 Grade 10 students from selected public secondary schools in Quirino Province during School Year 2024–2025. Data were gathered using the validated Environmental Awareness and Practices Questionnaire (EAPQ) and were analyzed using frequency, percentage, mean, and standard deviation. Findings revealed that the respondents were equally distributed by sex, were represented across small, medium, large, and mega schools, and were slightly more drawn from urban schools. The students were generally aware of the five YES-O domains, with the highest awareness observed in Gulayan sa Paaralan, followed by Awareness and Outreach Programs and Solid Waste Management, Entrepreneurship, and Energy Conservation, while School Inside a Garden and Partnerships and Linkages obtained relatively lower awareness ratings. In terms of environmental practices, the students generally seldom practiced environmental activities across the YES-O domains, although they more often engaged in Solid Waste Management, Entrepreneurship, and Energy Conservation, Gulayan sa Paaralan, and Awareness and Outreach Programs, while School Inside a Garden and Partnerships and Linkages showed lower levels of actual practice. The findings indicate that students demonstrate stronger awareness and participation in visible, routine, and school-based environmental activities than in technical, monitoring, and externally linked environmental initiatives.